Discovery and characterization of antilisterial proteins from Paenibacillus polymyxa Kp10 using genome mining and mass spectrometry for food application - Khairil Mokhtar, Nur Fadhilah (2021)
The prevalence of food poisoning cases causing listeriosis is worrisome, requiring advancement in food preservation strategies. The use of chemical preservatives raises health concern, therefore prompted the search of new natural preservatives such as bioactive proteins. A variety of bacteria isolated from dairy and fermented products have been known to produce various antimicrobial proteins beneficial for food and pharmaceutical industries. Previously, unidentified pure bacterial isolate originated from milk curd has been found to exert antimicrobial activity against Listeria monocytogenes ATCC 15313. Despite promising property exerted by the bacteria, the protein(s) responsible for the antilisterial activity was not yet identified and characterized, which mask its true potential for industrial application. The bacterium is hypothesized to encode antimicrobial genes in its genome and expresses one or more antilisterial proteins with a varying degree of stability against various conditions. Hence, this study aimed to identify the bacterium, followed by identification and characterization of potential genes and proteins contributing to the bacterial antilisterial property. Genome mining strategies in combination with mass spectrometric analysis were conducted to predict and identify the antilisterial proteins. The antilisterial activity of these proteins was verified through heterologous protein expression in Escherichia coli, followed by physicochemical stability assays against different pH, temperature and proteases. 16S rDNA sequence analysis of the pure isolate confirmed its identity as Paenibacillus polymyxa and designated as P. polymyxa Kp10. Genome mining of the bacterial draft genome sequence successfully determined eight putative ribosomally-synthesized antimicrobial proteins and six non-ribosomally synthesised antimicrobial peptide/polyketides. Out of the fourteen predicted proteins and peptides, two histone-like DNA binding proteins HU precedingly detected in silico were identified by the mass spectrometric analysis of the partially purified antilisterial proteins. Additionally, the active fraction also contains translation initiation factor IF-1 and a 50S ribosomal protein L29. All of the antilisterial proteins produced by P. polymyxa Kp10 exhibited a various degree of physicochemical stability against different pH, temperature, proteases, and in the meat homogenates. Overall, the proteins are stable at high temperature, but sensitive to proteases and high alkaline pH. Proteins’ stability in chicken, salmon and Ultra High Temperature (UHT) processed-milk was significantly compromised but excellent stability was observed in beef and simulated meat gravy food model. Bactericidal action of the proteins was confirmed by their ability to reduce and totally inhibit the growth of L. monocytogenes in simulated meat gravy food model. This study highlighted the potential of antimicrobial proteins and peptides from P. polymyxa Kp10 for manipulation in food industry, which warrants further investigations.